VIGS approach reveals the modulation of anthocyanin biosynthetic genes by CaMYB in chili pepper leaves - Zhang, Zhen; Li, Da-Wei; Jin, Jing-Hao; Yin, Yan-Xu; Zhang, Huai-Xia; Chai, Wei-Guo; Gong, Zhen-Hui (Frontiers in Plant Science, 2015)
The purple coloration of pepper leaves arises from the accumulation of anthocyanin. Three regulatory and 12 structural genes have been characterized for their involvement in the anthocyanin biosynthesis. Examination of the abundance of these genes in leaves showed that the majority of them differed between anthocyanin pigmented line Z1 and non-pigmented line A3. Silencing of the R2R3-MYB transcription factor CaMYB in pepper leaves of Z1 resulted in the loss of anthocyanin accumulation. Moreover, the expression of multiple genes was altered in the silenced leaves. The expression of MYC was significantly lower in CaMYB-silenced leaves, whereas WD40 showed the opposite pattern. Most structural genes including CHS, CHI, F3H, F3’5’H, DFR, ANS, UFGT, ANP and GST were repressed in CaMYB-silenced foliage with the exception of PAL, C4H and 4CL. These results indicated that MYB plays an important role in the regulation of anthocyanin biosynthetic related genes. Besides CaMYB silenced leaves rendered more sporulation of Phytophthora capsici Leonian indicating that CaMYB might be involved in the defense response to pathogens.